KAJIAN PENENTUAN LUAS TANAH DENGAN BERBAGAI METODE - Aji, Seno (JURNAL AGRI-TEK, 2014)
In general the measurement of land area can be used several simple tools. While for the measurement an accurate of land area then required a tools measurement namely theodolit. The resulting data from the measurements of theodolite which was horizontal angle, vertical angle, upper stadia, center stadia, lower stadia, and horizontal distance. There are several kinds of ways or method of determining the land area by counting broad in manner divide into several triangles, by counting coördinate, and by help program mapinfo 8.5. A method of calculating the land area by using program mapinfo 8.5 used as a reference method another in determination of the land area. To method of dividing the extent of land into several triangular obtained result is 1473,93 m2 and prosentase preciseness is 99,59 %. The method of calculating the land area by coördinate method obtained result is 1472,38 m2, and prosentase preciseness is 99,49 %. While the method of calculating the land area by using program mapinfo 8.5 obtained result is 1480 m2 with prosentase preciseness equal to 100 %.Keyword: the measurement, the land area, theodolite, program mapinfo 8.5.